Peran Kereta Api Indonesia (KAI) sebagai Infrastruktur Transportasi Wilayah Perkotaan - Ketut Biomantara; Herdis Herdiansyah (Universitas Bina Sarana Informatika, 2019)
Transportation is an important part of human life. Transportation is the driving force for socio-economic activities that must be accessible to all people. Transportation access is the heart of the development of an area, if transportation access is easy then the development of an area is easier to achieve. One of the most popular means of transportation in Indonesia and being a mass transportation that is very effective for human and goods mobilization is the train. So that the existence of train access can be a determining factor and support the accessibility of an area. This research was conducted to determine the role of trains in supporting the accessibility of the region. Research data collection was carried out by conducting observations, interviews, and literature reviews. Based on the results of the study it was found that since the first time it was built by the Dutch East Indies government in 1864, 26 km in the Kemijen Tanggung area currently has 25,361 employees. The vision is to become the best rail service provider that focuses on customer service and meets stakeholder expectations. Good and smooth transportation growth is a collaboration between three supporting forces in the form of good spatial planning, policies or regulations in the field of road network infrastructure and multi-modal transport, road traffic behavior and law enforcement. PT. KAI tries to give choices so that the community is fulfilled its accessibility in carrying out activities to the destination